Công ty có rủi ro thao túng số liệu kế toán cao hơn liệu có tránh thuế nhiều hơn? Bằng chứng dựa trên chỉ số Beneish M-score và thuế suất hiệu dụng từ thị trường mới nổi Việt Nam - Phạm Thị Hồng, Quyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the relationship between accounting manipulation risk and tax avoidance in Vietnamese non-financial listed companies from 2016 to 2023. Tax avoidance was measured using the accounting effective tax rate (ACE) and the cash flow effective tax rate (CFE), whereas the Beneish M-score assessed manipulation risk. Using panel data, the GLS model was employed to account for heteroskedasticity with industry-year fixed effects. The results showed that the M-score was negatively correlated with ACE but positively correlated with CFE, implying that the relationship between manipulation risk and tax behavior depends on whether tax is measured using accounting-based indicators reported in financial statements or cash-based indicators reflecting actual tax payments. Robustness tests using Winsorization confirmed that the signs and statistical significance of the results remained stable. The study provides empirical evidence contributing to the complementarity–trade-off debate in emerging markets, with implications for tax authorities, firms, investors, and auditors.
Keywords: Beneish M-score; Earnings manipulation risk; Effective tax rate; Corporate tax avoidance